Timing system design and tests for the Gravity Probe B relativity mission. (17th November 2015) - Li, J; Keiser, G M; Lockhart, J M; Ohshima, Y; Shestople, P
Abstract: In this paper, we discuss the timing system design and tests for the NASA/Stanford Gravity Probe B (GP-B) relativity mission. The primary clock of GP-B, called the 16 f o clock, was an oven-controlled crystal oscillator that produced a 16.368 MHz master frequency1 . The 16 f o clock and the 10 Hz data strobe, which was divided down from the 16 f o clock, provided clock signals to all GP-B components and synchronized the data collection, transmission, and processing. The sampled data of science signals were stamped with the vehicle time, a counter of the 10 Hz data strobe. The time latency between the time of data sampling and the stamped vehicle time was compensated in the ground data processing. Two redundant global positioning system receivers onboard the GP-B satellite supplied an external reference for time transfer between the vehicle time and coordinated universal time (UTC), and the time conversion was established in the ground preprocessing of the telemetry timing data. The space flight operation showed that the error of time conversion between the vehicle time and UTC was less than 2 μ s. Considering that the constant timing offsets were compensated in the ground processing of the GP-B science data, the time latency between the effective sampling time of GP-B science signals and the stamped vehicle time was verified to within 1 ms in the ground tests.